Low‐Temperature Thermal CVD of Superblack Carbon Nanotube Coatings. Issue 18 (30th May 2017) - Basheer, Hameeda Jagalur; Pachot, Charlotte; Lafont, Ugo; Devaux, Xavier; Bahlawane, Naoufal
Abstract : The deposition of carbon nanotube (CNT) coatings via thermal chemical vapor deposition (CVD) is intensively reported. The surface acidity, chemical nature of the catalytic nanoparticles, and the carbon precursor are highly inter‐related key parameters. Furthermore, reducing the typical high‐growth temperature requires the implementation of toxic and hazardous organic precursors. In this study, the growth of CNT coatings is demonstrated using a single‐step CVD process in which magnesium oxides, material with enhanced basicity, and nanoparticles of cobalt are codeposited. This deposit catalyzes simultaneously the decomposition of ethanol to spark the growth of CNTs. The deposition is successively performed at 330–500 °C. Grown CNTs below 400 °C feature a high defect concentration and large diameters, 20 nm, relative to those obtained at ≥400 °C with no apparent defects and diameter of 12 nm. In terms of optical properties, films grown at ≥400 °C reflect less than 0.5% of light in the UV–vis–near IR, and exhibit a Lambertian behavior. Furthermore, the bidirectional reflectance distribution function measurements reveal identical optical properties irrespective of the underlying substrate. Therefore, the process holds a great potential for applications involving stray light reduction. Abstract : Thermal chemical vapor deposition is implemented in this study to grow carbon nanotubes (CNTs). The single step process enables the deposition of Co and MgO composite that sparks the conversion of ethanol to CNT. The process is kinetically controlled within the entire investigated temperature range 330–500 °C, and the resulting films feature superblack properties with high potential for optical instruments.